Homework for New Changes in The Future: A Bibliometric Analysis - Andika Wulan Febriani; Madziatul Churiyah (Profesional Muda Cendekia Publishing, 2022)
This literature review focuses on the relationship between working from home (WFH) and the new future order. The method employed is a bibliometric literature review that was examined using VOSviewer software. The VOSviewer software analysis technique was used to assess papers produced via the Scopus database and utilized as a reference for researchers. The findings of 315 papers were cited from 2020 to 2022, with just 40 articles being evaluated. The researchers then clarified and visualized co-authorship, co-accurance, and citation using VOSviewer softwareThis literature review, as a whole, provides a reliable starting point for additional research on the topic at hand. Working from home refers to a variety of methods of working that are common among today's workers. Working from home is a flexible and automated work method that allows employees to work from home via telecommuting, teleworking, and remote work by leveraging modern digital technology tools as a bridge to work. All men and women between the ages of 25 and 60 can work from home. Working flexibly in the